STEAM Integrated Project Based Learning Exploration Against Understanding the Concept of Static Fluids - Shapna D. Atika; Debora N. Sudjito; Prima Warta Santhalia (Postgraduate, University of Mataram, 2023)
Conceptual understanding is the capacity to grasp a variety of learning resources in which pupils are able to not only recognize and know the concepts, but also re-express them in a way that is easier to understand and apply. Students' conceptual comprehension skills in STEAM-integrated Project Based Learning on static fluid materials are the focus of this study. This study was carried out with the use of an embedded experimental model of mix methods. The participants in this study are 36 senior high school students of grade XI in Salatiga. Students' concept understanding exam scores at the pre-test and post-test were used to generate quantitative data. The test scores were examined using the statistical description test, normality test, t-test, N-Gain score, and Effect size. Qualitative data was gathered through students’ interviews following the completion of the pre- and post-tests, it was analyzed using Abraham's concept understanding level category (1992). There is improvement of students’ conceptual understanding, i.e. 16,66% students improved from partially understand to understand; 66,66% students improved from partially misconception to partially understand; and 16,66% students improved from misconception to partially misconception. Thus, the conceptual understanding of most of the students improved after they experience STEAM-based Project Based Learning